Storage Conditions and Immunoreactivity of Breast Cancer Subtyping Markers in Tissue Microarray Sections. Issue 4 (April 2020) - Omilian, Angela R.; Zirpoli, Gary R.; Cheng, Ting-Yuan David; Yao, Song; Stein, Leighton; Davis, Warren; Head, Karen L.; Nair, Priya; Khoury, Thaer; Ambrosone, Christine B.; Bshara, Wiam
Abstract : Loss of immunoreactivity in tissue sections has been shown to occur when slide sections are stored at room temperature for prolonged periods of time. We conducted a systematic investigation to determine the extent of staining loss in various storage conditions to determine an optimal storage method. We investigated 6 antibodies that are commonly used for breast cancer subtyping in research studies with immunohistochemistry (ER, PR, HER2, CK5/6, EGFR, and Ki67) in formalin-fixed paraffin-embedded breast tissue microarrays consisting of 148 patients. Tissue microarrays were sectioned at various time points: fresh, 1 week, 1 month, 6 months, and 12 months before staining. Slides sectioned at each time point were stored in 5 storage conditions: desiccator, paraffin dipped, 4°C, −20°C, and −80°C. Immunohistochemistry scores were assessed over time with McNemar Test and Bowker Test of Symmetry. Desiccator storage was the only storage condition that did not show any loss in immunoreactivity for any antibody or time point in our study. Paraffin coated slides were the most difficult storage method operationally and also showed the most loss in immunoreactivity. Storing sections in a desiccator was the most effective method for minimizing immunoreactivity loss. Cold storage at 4°C is an intermediate option that is not as protective as a desiccator, but offers the advantage of being accessible to virtually all research labs. Abstract : Supplemental Digital Content is available in the text.